Daily Life Positive Events Predict Well-Being Among Depressed Adults 10 Years Later. (March 2021) - Panaite, Vanessa; Devendorf, Andrew R.; Kashdan, Todd B.; Rottenberg, Jonathan
Relatively little is known about the links between the events and emotions experienced in daily life and long-term outcomes among people diagnosed with depression. Using daily diary data from the Midlife Development in the United States, we examined how positive daily life events and emotions influence long-term (10 years later) depression severity and well-being. Participants met criteria for major depressive disorder ( n = 121) or reported no depression ( n = 839) over the past 12 months. Participants reported positive events, socializing activities, and negative affect (NA) and positive affect (PA) for 8 consecutive days. Relative to nondepressed adults, depressed adults reported fewer positive events (fewer positive interactions, spending less time with others), lower PA, and higher NA. Among initially depressed adults, higher baseline well-being was related to higher daily PA, lower NA, and fewer days with less reported social time; higher daily PA and positive interactions predicted higher well-being 10 years later ( N = 77). Variations in day-to-day events and emotions among people with depression may presage psychological functioning years later.